Experimental mastitogenicity of Mollicutes originated from bovines with reproductive disordets in rat mammary gland model - SINGH, Y; GARG, D N; MAHAJAN, S K; KAPOOR, P K (The Indian Journal of Animal Sciences, 2013)
Rat mammary gland model was used to test mastitogenicity of Mollicutes (Mycoplasma. Acholeoplasma) from various bovine reproductive disorders. The progress of infection was monitored in terms of gross and histopathological lesions of mamary tissues and reisolation of inoculated ,mollicutes at necropsy. The tested Mollicutes could be categorized into 2 groups: (i) M mycoides subsp. mycoides (LC), M. bovis. M.bovigenitalium. M.bovoculi. M.arginini (type strain G-230), A.granulanlm as mastitogenic, and (ii) A. axanthum, A.laidlawii. A.oculiÂ·and M.sp. (ungrouped) as non-mastitogenic to rat mammary gland. Thus rat-mammary gland model is recommended for use as a suitable and economical model for determining the mastitogenicity of mollicutes.